Incorporating Reference into A Unified Service Point at an Academic Library: A Case Study. Issue 4 (2nd October 2019) - Megwalu, Anamika; Barron, Kate
ABSTRACT: This paper aims to discuss the incorporation of reference services into a trending service point model called the Unified Service Point (USP). Driven by organizational shift, the model was recently adopted by Dr. Martin Luther King, Jr. Library of San Jose State University. An anonymous survey was conducted to understand student perspectives on reference services, including the USP. The survey also asked questions about student motivation for seeking help from a librarian, and their level of satisfaction with the reference services. The authors offer recommendations to improve reference services at the USP based on the results of the study.